PENGARUH BEBAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN: (STUDI PADA KARYAWAN PT MEISA AGRO PERKASA PURWAKARTA) - Ratna Winarni; Jaelani Jaelani (MANAJEMEN, 2025)
This study aims to analyze the influence of workload and work discipline on employee performance at PT. Meisa Agro Perkasa. The research instrument was tested through validity and reliability tests, with all items declared valid and reliable. The classical assumption test showed that the data were free from multicollinearity, heteroscedasticity, and normally distributed. The results of multiple linear regression analysis indicate that workload and work discipline significantly influence employee performance. Partially, work discipline has a positive and significant effect on performance, while workload is also significant but interpreted as having a negative effect. The F-test indicates that both independent variables simultaneously influence employee performance. The adjusted R² value of 0.590 indicates that 59% of the variation in employee performance can be explained by these two variables. This study emphasizes the importance of workload management and improving work discipline to support employee productivity and effectiveness in the company.